Consumer Decision Model: Online Customer Reviews, Online Customer Ratings, and Brand Ambassadors Influence Decisions to Purchase in E-commerce During the COVID-19 Pandemic - Salsabela Amalia; Titi Nugraheni; Misdiyono Misdiyono (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2024)
This study aims to determine the effect of Online Customer Reviews, Online Customer Rating, and Brand Ambassador on Purchasing Decisions during the Covid-19 Pandemic on Tokopedia E-Commerce and to determine which variables are most dominant in influencing consumer purchasing decisions during the Covid-19 pandemic that occurred in Indonesia in 2020. The analysis method in this study uses quantitative primary data by distributing questionnaires via Google Forms. The test stages carried out are validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t-test, f-test, and determination coefficient analysis. The testing tool used is SPSS version 26. The results of this study indicate that online customer reviews and online customer ratings do not have a significant effect on purchasing decisions, while brand ambassadors have a significant effect on purchasing decisions.